2013
DOI: 10.1007/s12098-013-1067-y
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Rapid Antigen Detection Testing in Group A Beta-Hemolytic Streptococcal Tonsillopharyngitis

Abstract: The low sensitivity of the RADT may be related to streptococcal carriage in some patients. The throat culture should be repeated after treatment to detect streptococcal carriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…Strategy used by parents: distraction (25%), drink more fluids (23%), giving preferred foods (18%) Sharp 2013 59 Correlation between FS and problem behaviors (negative vocalizations and disruptions during the meal) ( p <0.05) No correlation between ASD symptom severity and FS Suarez 2013 63 Stable FS rate and severity and its association with sensory sensitivity across the time over a period of two years Sun 2013 51 FS 43.4% ( p =0.003). Higher resistance in trying new foods ( p <0.001) and inferior eating independence ( p <0.0001) Crasta 2014 31 Feeding problem more prevalent (61%) and severe ( p <0.001); more prevalent in ASD children younger than 6 years ( p = 0.01); higher disruptive meal-time behaviors ( p = 0.02) and food over-selectivity ( p= 0.001); significant correlations with sensory measures ( p <0.05), and autism severity ( p =0.01) Field 2014 23 No differences in being breastfed at least four months George 2014 24 Association with breastfeeding duration (nil/less than 6 months) ( p <0.001) Goldin 2014 64 No differences neither in under-eating nor over-eating Johnson 2014 65 Association ( p <0.001) between feeding problems and repetitive and ritualistic behaviors, sensory measures, and externalizing and internalizing behavior; lack of association with social and communication deficits, autism severity, and cognitive levels Kral 2014 75 Greater food avoidance behaviors, including reluctance to eat novel foods ( p =0.004), being selective about the range of foods they accept ( p =0.03), in ASD children with atypical oral sensory sensitivity than ASD children with typical oral sensory sensitivity Attlee 2015 49 …”
Section: Resultsmentioning
confidence: 99%
“…Strategy used by parents: distraction (25%), drink more fluids (23%), giving preferred foods (18%) Sharp 2013 59 Correlation between FS and problem behaviors (negative vocalizations and disruptions during the meal) ( p <0.05) No correlation between ASD symptom severity and FS Suarez 2013 63 Stable FS rate and severity and its association with sensory sensitivity across the time over a period of two years Sun 2013 51 FS 43.4% ( p =0.003). Higher resistance in trying new foods ( p <0.001) and inferior eating independence ( p <0.0001) Crasta 2014 31 Feeding problem more prevalent (61%) and severe ( p <0.001); more prevalent in ASD children younger than 6 years ( p = 0.01); higher disruptive meal-time behaviors ( p = 0.02) and food over-selectivity ( p= 0.001); significant correlations with sensory measures ( p <0.05), and autism severity ( p =0.01) Field 2014 23 No differences in being breastfed at least four months George 2014 24 Association with breastfeeding duration (nil/less than 6 months) ( p <0.001) Goldin 2014 64 No differences neither in under-eating nor over-eating Johnson 2014 65 Association ( p <0.001) between feeding problems and repetitive and ritualistic behaviors, sensory measures, and externalizing and internalizing behavior; lack of association with social and communication deficits, autism severity, and cognitive levels Kral 2014 75 Greater food avoidance behaviors, including reluctance to eat novel foods ( p =0.004), being selective about the range of foods they accept ( p =0.03), in ASD children with atypical oral sensory sensitivity than ASD children with typical oral sensory sensitivity Attlee 2015 49 …”
Section: Resultsmentioning
confidence: 99%
“…Gurol et al reported RADT sensitivity and specificity 64.6 and 96.7% 30 in 892 children with a mean age of 5.3 years, while Küçük et al reported a sensitivity and specificity of 59.5 and 97.2%. 31 The lack of a standardized culture method as the reference test may be another explanation for the variation in sensitivity between studies. 25,29,32 However, assessments of performance characteristics of the tests, especially their sensitivity, are not standardized in the literature due to the numerous culture techniques, which cannot be compared.…”
Section: Resultsmentioning
confidence: 99%
“…Türkiye odaklı diğer bir araştırmada ise farklı bit kit ile çalışılmış SHAT duyarlılığı %68,1, özgüllüğü %92,2 bulunmuştur [2] . Altı yüz otuz dokuzu 0-6 yaş ve 253'ü 7-17 yaş arasında olan iki farklı çocuk grubunu inceleyen bir çalışmada ise SHAT duyarlılığı ve özgüllüğü sırasıyla %59,5 ve %97,2 bulunmuştur [18] . Bu değerlerin, %58 duyarlılık ve %91 özgüllük ile bizim çalışmamıza paralel olduğu görülmüştür.…”
Section: Discussionunclassified
“…SHAT duyarlılık ve özgüllüğünü etkileyen en önemli faktörlerden biri eküvyon çubuktan teste aktarılan inokulum miktarıdır. Diğer faktörler ise farklı laboratuvar kitlerinin kullanımı, testi uygulayanın becerisi, bölgedeki AGBHS prevalansı ve örnek alım tekniği olarak sayılabilir [4,18] . Çalışmamızda kullanılan testin saptadığımız duyarlılık ve özgüllük değerlerine, yukarıda bahsedilen faktörlerin etki ettiğini düşünmekteyiz.…”
Section: Discussionunclassified